Intra-articular corticosteroid injections for the treatment of hip and knee osteoarthritis-related pain: Considerations and controversies with a focus on imaging-radiology scientific expert panel - Guermazi, Ali; Neogi, Tuhina; Katz, Jeffrey N.; Kwoh, C. Kent; Conaghan, Philip G.; Felson, David T.; Roemer, Frank (Radiology, 2020)
Current management of osteoarthritis (OA) is primarily focused on symptom control. Intra-articular corticosteroid (IACS) injections are often used for pain management of hip and knee OA in patients who have not responded to oral or topical analgesics. Recent case series suggested that negative structural outcomes including accelerated OA progression, subchondral insufficiency fracture, complications of pre-existing osteonecrosis, and rapid joint destruction (including bone loss) may be observed in patients who received IACS injections. This expert panel report reviews the current understanding of pain in OA, summarizes current international guidelines regarding indications for IACS injection, and considers preinterventional safety measures, including imaging. Potential profiles of those who would likely benefit from IACS injection and a suggestion for an updated patient consent form are presented. As of today, there is no established recommendation or consensus regarding imaging, clinical, or laboratory markers before an IACS injection to screen for OA-related imaging abnormalities. Repeating radiographs before each subsequent IACS injection remains controversial. The true cause and natural history of these complications are unclear and require further study. To determine the cause and natural history, large prospective studies evaluating the risk of accelerated OA or joint destruction after IACS injections are needed. However, given the relatively rare incidence of these adverse outcomes, any clinical trial would be challenging in design and a large number of patients would need to be included.
CRIS-Team Scopus Importer:2020-11-27